2022
DOI: 10.1126/sciadv.abg9055
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear HMGB1 protects from nonalcoholic fatty liver disease through negative regulation of liver X receptor

Abstract: Dysregulations of lipid metabolism in the liver may trigger steatosis progression, leading to potentially severe clinical consequences such as nonalcoholic fatty liver diseases (NAFLDs). Molecular mechanisms underlying liver lipogenesis are very complex and fine-tuned by chromatin dynamics and multiple key transcription factors. Here, we demonstrate that the nuclear factor HMGB1 acts as a strong repressor of liver lipogenesis. Mice with liver-specific Hmgb1 deficiency display exacerbate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…In the therapeutic context, silencing HMGB1 may result in losing its critical nuclear housekeeping function in host cells. Personnaz et al 39 reported that liver-specific HMGB1-deficient mice exhibited exacerbated hepatic steatosis. An alternative approach is to improve the intracellular distribution of HMGB1 by increasing SIRT1 expression or activity to retain HMGB1 in the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…In the therapeutic context, silencing HMGB1 may result in losing its critical nuclear housekeeping function in host cells. Personnaz et al 39 reported that liver-specific HMGB1-deficient mice exhibited exacerbated hepatic steatosis. An alternative approach is to improve the intracellular distribution of HMGB1 by increasing SIRT1 expression or activity to retain HMGB1 in the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of Hmgb1 gene in hepatocytes also enhanced Lxrα and Pparγ expression. In contrast, Hmgb1 overexpression in liver protected mice from HFD-induced hepatic steatosis [ 66 ].…”
Section: Gastrointestinal Ev-containing Substances Are Associated Wit...mentioning
confidence: 99%
“…However, miR-206 was decreased in the livers of mice fed an HFD, and increasing miR-206 in the liver played a protective role in inhibiting lipid production ( 92 ). In addition, the increase in Lxrα could protect against hepatic steatosis ( 94 ). This is contradictory, but it also shows the multidirectional regulation of miR-206.…”
Section: Role Of Mirnas In Lipid Metabolism In Offspringmentioning
confidence: 99%